KEPEMIMPINAN TRANSFORMASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DALAM MENINGKATKAN KINERJA GURU - Sri Suratiyah (STAI Syubbanul Wathon Magelang, 2018)
Efforts to provide educational stimuli and develop every potential ofchildren, requires the existence of teacher roles and performance that isto support the success of early childhood in developing creativity andall the potential that exists in children. Teachers are the most influentialcomponent to the creation of quality education processes and results.Based on this, this study aims to examine the effect of teachers'perceptions on transformational leadership and OrganizationalCitizenship Behavior (OCB) on teacher performance. This study usesquantitative approach with the number of research subjects whichamounted to 79 consisting of PAUD teachers in District Sedayu. Themethod of analysis used this research is multiple linier regressionanalysis. The results found that the perception of transformationalleadership and organizational citizenship behavior had a positive andsignificant influence on teacher performance. In addition, the study alsofound that transformational leadership perceptions have greaterinfluence on teacher performance when compared to the effects oforganizational citizenship behavior on teacher performance.